Ways of shipping costs’ reduction - Redina, I. V.; Редина, И. В.; Редіна, І. В. (Одеса : Фенікс, 2014)
Improving of the transport network for bilateral cargo traf¬fic between markets and internal parts of the country allows attracting more cargo to the ports. Not only economy of scale in port operations is achieved. Attraction of larger vessels with lower specific transportation costs or new sup¬pliers of alternative service shipping is also potential.
Redina, I. V. Ways of shipping costs’ reduction / I. V. Redina // Правове життя сучасної України: матеріали Міжнар. наук. конф. проф.-викл. та аспірант. складу / відп. за вип. В. М. Дрьомін; НУ ОЮА, Півд. регіон. центр НАПрН України. – Одеса: Фенікс, 2014. – Т. 2. – С. 419-421.
Keywords: ways of shipping costs’ reduction; пути снижения цен перевозки груза; шляхи зниження цін перевезення вантажу